A Speech Acts Analysis of English COVID-19 News Headlines: مثنى نجيب المرسومي, جمعة قادر حسين (Journal of the College of Education for Women, 2021)
News headlines are key elements in spreading news. They are unique texts written in a special language which enables readers understand the overall nature and importance of the topic. However, this special language causes difficulty for readers in understanding the headline. To illuminate this difficulty, it is argued that a pragmatic analysis from a speech act theory perspective is a plausible tool for a headline analysis. The main objective of the study is to pragmatically analyze the most frequently employed types of speech acts in the news headlines covering COVID-19 in Aljazeera English website. To this end, Bach and Harnish's (1979) Taxonomy of Speech Acts has been adopted to analyze the data. Thirty headlines have been collected from Aljazeera English news website. The findings have shown that constatives and directives occur more frequently than commissives. Other types, like acknowledgments, effectives and verdictives are not employed. The study has concluded that to pay a special emphasis on COVID-19 as an issue that preoccupied and endangered the world, headline writers of Aljazeera website uses specific speech acts, constatives and directives, more frequently than others. This makes it clear that using specific speech acts in writing headlines is an effective way for inspiring readers to easily understand the intended message.